SISTEM INFORMASI PUBLIKASI BPR SINARARTA SEJAHTERA BERBASIS WEB - JOKO PURNOMO; WIKA PURBASARI; NOVITA SETIANTI; AHMAD ARIFIN (LPPM STMIK Widya Utama, 2023)
Abstract _ The study, titled the Web-based Information System for Rural Bank Credit People (BPR) Sinararta Sejahtera, is design a web-based application that can be utilized in the banking world, especially in the BPR environment. This application is able to be a medium of information and communication to OJK, customers, bank / bpr owners, managers and the public. Rapid Application Development (RAD) system development method was chosen as a system development method in this study because the system can be developed within 90 days. The users are directly involved when developing the system so that the system is developed according to user needs. Unified Modeling Language (UML) has anumber of system imaging models that will be developed to be used at the design process stage in RAD. The product testing in this study uses the Dimension of Quality for Goods attribute and the benefit test in this study uses the ULEA variable by 30 respondents. The results of the research prove that the use of the Basis Sinararta Sejahtera Information System Web-Based Publication can be used as a medium for channeling information and communication to OJK, customers, bank owners / bpr, managers and the public. Keywords : Publication, RAD, UML, ULEA